Transition Réussie des Services Hospitaliers vers Les Nouvelles Professions du Système LMD. Besoins en Compétences et Perspectives des Parties Prénantes en République Démocratique du Congo. - Bwalya , Richard Peti (Human Resource and Leadership Journal, 2025)
Purpose: The article explores the skills needs and perspectives of stakeholders to successfully transition hospital services to the Bachelor-Master-Doctorate (LMD) system in the Democratic Republic of the Congo (DRC). The goal is to align the competencies of healthcare professionals with the requirements of the new professions introduced by this reform. Methodology: The study uses a qualitative approach with semi-structured interviews conducted with 852 healthcare professionals, educators, and students. Data were analyzed using software such as Jamovi to generate frequency tables and thematic analyses. Findings: The findings reveal a predominantly negative perception of current hospital services, characterized by a lack of funding, infrastructure, and qualified personnel. While the new professions within the LMD system are generally viewed positively, their adoption is hindered by insufficient institutional preparation and gaps in managerial and practical skills. There is a strong need for continuous training and technology. Unique contribution to theory: The study contextualizes the academic and professional transition in a resource-limited country, highlighting the importance of a participatory systemic approach to align academic training with professional requirements. It proposes recommendations to integrate modern pedagogical methodologies, improve hospital governance, and strengthen infrastructure.